Chapter 1 Introduction - Hirvonen, Helena (Taylor & Francis, 2022)
Digital technologies shape our embodied lives and affect our knowledge of the self and the world. The introductory chapter of the book presents the state of the art in the research on digitalisation of health and social care work, with a focus on care for older people. In ageing societies, understanding what it takes to introduce and use digital technologies can pave the way to a successful, sustainable, and equally accessible system of social care and healthcare provision for older people. The chapter discusses some of the limitations in the present discussion and how the book at hand aims to address these gaps. The chapter proposes that living in an increasingly digitalised world requires digital agency, that is the individual's ability to control and adapt to their surroundings, and to critically address technological determinism in the everyday life. The chapter ends with an overview of the book's subsequent chapters that demonstrate different aspects to service users' and care workers' digital agency based on recent studies of digital technologies in care for older people.